Potential predictive and therapeutic applications of small extracellular vesicles-derived circPARD3B in osteoarthritis - Zhiguo Lin; Yeye Ma; Xiaoying Zhu; Siming Dai; Wentian Sun; Wenjing Li; Sijia Niu; Maolin Chu; Juan Zhang (Frontiers Media S.A., 2022)
Background: Heterogeneous phenotypes that display distinct common characteristics of osteoarthritis (OA) are not well defined and will be helpful in identifying more customized therapeutic options for OA. Circular RNAs (circRNAs) have attracted more and more attention due to their role in the progression of OA. Investigating the role of circRNAs in the pathogenesis of OA will contribute to the phenotyping of OA and to individualized treatment.Methods: Small extracellular vesicles (sEV) were isolated from serum samples from patients with OA of different stages and sEV-derived circPARD3B was determined using RT-qPCR analysis. CircPARD3B expression in a stimulated coculture that included OA fibroblast-like synoviocytes (OA-FLS) as well as human dermal microvascular endothelial cells (HDMECs), plus the effects of circPARD3B on the expression of vascular endothelial growth factor (VEGF) long with angiogenic activity, were evaluated in vitro. Based on bioinformatics analysis and luciferase reporter assay (LRA), MiR-326 and sirtuin 1 (SIRT1) were found to be interactive partners of circPARD3B. Mesenchymal stem cells (SMSCs) overexpressing circPARD3B were constructed and SMSCs-derived sEV with overexpressed circPARD3B (OE-circPARD3B-SMSCs-sEV) were obtained to explore the effect of the intervention of circPARD3B combined with SMSCs-sEV-based therapy in vitro and in a OA model induced by collagenase in vivo.Results: Serum sEV-linked circPARD3B was indentified to be significantly decreased in the inflammatory phenotype of OA. Overexpression of circPARD3B was found to inhibit the expression of VEGF, as well as the angiogenesis induced by VEGF in a IL-1β stimulated the co-culture of OA-FLS as well as HDMECs. CircPARD3B is directly bound to miR-326. SIRT1 was considered a novel miR-326 target gene. OE-circPARD3B-SMSCs-sEV significantly reduced VEGF expression in coculture of OA-FLS and HDMECs. Injection of OE-circPARD3B-SMSCs-sEV could also reduce synovial VEGF; additionally, it could further ameliorate OA in the mouse model of OA in vivo.Conclusion: Serum sEV circPARD3B is a potential biomarker that enables the identification of the inflammatory phenotype of patients with OA. Correspondingly, intracellular transfer of circPARD3B through OE-circPARD3B-SMSCs-sEV could postpone disease progression through a functional module regulated angiogenesis of circPARD3B-miR-326-SIRT1, providing a novel therapeutic strategy for OA.